Pro-Resolving Mediators in Regulating and Conferring Macrophage Function - Dalli, Jesmond; Serhan, Charles N. (Frontiers in Immunology, 2017)
Macrophages are central in coordinating the host response to both sterile and infective insults. Clearance of apoptotic cells and cellular debris is a key biological action preformed by macrophages that paves the way to the resolution of local inflammation, repair and regeneration of damaged tissues and re-establishment of function. The essential fatty acid-derived autacoids termed specialized pro-resolving mediators (SPM) play central roles in promoting these processes. In the present article, we will review the role of microvesicles in controlling macrophage efferocytosis and SPM production. We will also discuss the role of both apoptotic cells and microvesicles in providing substrate for transcellular biosynthesis of several SPM families during efferocyotsis. In addition, this article will discuss the biological actions of the recently uncovered the macrophage-derived SPM termed maresins. These mediators are produced via 14-lipoxygenation of docosahexaenoic acid that is either enzymatically converted to mediators carrying two hydroxyl groups or to autacoids that are peptide-lipid conjugates, coined maresin conjugates in tissue regeneration (MCTR). The formation of these mediators is temporally regulated during acute self-limited infectious inflammation where they promote the uptake and clearance of apoptotic cells, regulate several aspects of the tissue repair and regeneration and display potent anti-nociceptive actions.